THE ROLE OF ENTREPRENEURIAL PASSION FOR INVENTING AND FOUNDING IN DRIVING SME PERFORMANCE: EVIDENCE FROM FEMALE CULINARY ENTREPRENEURS IN MALANG CITY - Bintang Nurul Hidayati; Shoimatul Fitria; Astiwi Indriani; Foza Hadyu Hasanatina (STIE AMA Salatiga, 2026)
ABSTRACTThis study examines the effects of identity-based entrepreneurial passions (EP), specifically passion for inventing (EP for Inventing) and passion for founding (EP for Founding), on the performance of female-owned small and medium-sized enterprises (SMEs). The research employs cross-sectional data collected via questionnaires from 140 female-led culinary ventures in Malang, Indonesia. Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS software. The empirical results reveal that while passion for founding (EP for Founding) has a positive and statistically significant coefficient on firm performance, passion for inventing (EP for Inventing) does not exert a significant effect. These findings indicate that the administrative and structural drive to establish a business is a more critical driver of success for female entrepreneurs than product-centric innovation. This study advances the entrepreneurship literature by establishing that in emerging economies, the intrinsic psychological traits of female entrepreneurs, specifically the motivation to build and establish a business, serve as vital, self-sustaining cornerstones that directly propel enterprise growth.ABSTRAKPenelitian ini mengkaji pengaruh entrepreneurial passion (EP) berbasis idetitas, khususnya passion for inventing (semangat untuk berinovasi/menciptakan) dan passion for founding (semangat untuk mendirikan) terhadap kinerja usaha mikro, kecil, dan menengah (UMKM) yang dimiliki oleh perempuan. Penelitian ini menggunakan data lintas sektoral (cross-sectional) yang dikumpulkan melalui kuesioner dari 140 usaha kuliner yang dipimpin oleh pengusaha perempuan di Kota Malang, Indonesia. Analisis data dilakukan dengan menggunakan metode Structural Equation Modeling-Partial Least Squares (SEM-PLS) melalui perangkat lunak SmartPLS. Hasil empiris menunjukkan bahwa passion for founding memiliki pengaruh yang positif dan signifikan secara statistik terhadap kinerja UMKM. Sebaliknya, passion for inventing tidak menunjukkan pengaruh yang signifikan. Temuan ini mengindikasikan bahwa dorongan administratif dan struktural untuk mendirikan bisnis merupakan faktor penentu keberhasilan yang lebih krusial bagi pengusaha perempuan dibandingkan dengan inovasi yang berpusat pada produk. Penelitian ini berkontribusi pada literatur kewirausahaan dengan membuktikan bahwa di negara berkembang (emerging economies), karakteristik psikologis intrinsik dari pengusaha perempuan, khususnya motivasi untuk membangun dan mendirikan bisnis, berfungsi sebagai pilar mandiri yang dan berperan penting dalam mendorong pertumbuhan usaha secara langsung.